Spent tea leaves as extender and scavenger for urea formaldehyde-bonded plywood - Mari, Erlinda L.; Lapuz, Rebecca B.; Jimenez, Jr., Juanito P. (2018)
In lieu of wheat flour, spent tea leaves (STL) from the manufacture of tea-flavored drink was mixed with urea formaldehyde (UF) resin to produce an adhesive for 5-mm-thick plywood. Three glue mixes (GM1, GM2, and GM3) were formulated using three STL levels (3.4%, 6.8%, 10.2% by mass). GM1 had no catalyst and coconut shell flour/filler; GM2 had no catalyst but had a filler; while GM3 had a catalyst but no filler. The glue manufacturer?s recommended formulation was used for making the control plywood. All glue mixes were formulated with the same total resin solids. The effect of the STL on the various glue mixes was evaluated in terms of the plywood?s shear strength & wood failure (PNS ISO 12466-1:2016 & PNS ISO 12466-2:2016), and formaldehyde emission (PNS ISO 12460-4:2016). Results indicated that GM3, or complete replacement of wheat flour and coconut shell flour with STL both as extender and filler in the plywood glue mix, was the best formulation. It did not adversely affect the panel?s strength properties. Moreover, formaldehyde emission was significantly reduced by 36 to 60%.